1977
DOI: 10.1172/jci108678
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the mechanism of contralateral polyuria after renal artery stenosis.

Abstract: A B S T R A C T Acute renal artery stenosis in hydropenic dogs caused a contralateral increase in urine volume and free water clearance without change in glomerular filtration, renal blood flow, or osmolar clearance. The increase in urine volume was not dependent on the development of hypertension since it occurred in animals pretreated with trimethaphan but was dependent upon angiotensin since it was prevented with angiotensin blockade with Saralasin. The effect was not caused by angiotensin inhibiting antidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This notion was supported by the finding that the threshold concentration of angiotensin II needed to release prostaglandins from the kidney was in the range of that reported in patients with renovascular hypertension. 22 Further, Galvez et al 19 blocked the contralateral diuresis that follows ipsilateral arterial constriction with either angiotensin antagonists or blockers of prostaglandin synthesis. Thus, as hypertension progresses, ischemia in the stenotic kidney is diminished by a higher perfusion pressure, 23 rendering the stenotic kidney less dependent on synthesis of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…This notion was supported by the finding that the threshold concentration of angiotensin II needed to release prostaglandins from the kidney was in the range of that reported in patients with renovascular hypertension. 22 Further, Galvez et al 19 blocked the contralateral diuresis that follows ipsilateral arterial constriction with either angiotensin antagonists or blockers of prostaglandin synthesis. Thus, as hypertension progresses, ischemia in the stenotic kidney is diminished by a higher perfusion pressure, 23 rendering the stenotic kidney less dependent on synthesis of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be attributed to the earlier time at which we conducted our measurement. An increased urinary flow from the contralateral kidney was observed over a short period after renal artery stenosis by Galvez et al [15]. Also, DeForrest and co-workers studied separate renal functions in the two-kidney, one-clip hypertension model in dogs [16].…”
Section: Resultsmentioning
confidence: 95%
“…HHS is more frequently reported in patients with unilateral RAS. In patients with unilateral RAS corresponding to the 2-kidney-1-clip hypertension model [7], sustained renin secretion of the stenotic kidney with low perfusion and pressure natriuresis of the contralateral kidney are the main mechanisms to HHS development [4]. In the study by Agarwal et al [4], HHS was also reported in association with bilateral RAS in some patients.…”
Section: Discussionmentioning
confidence: 99%